Composition Light Concrete Composition and Properties - Nazarova, S.B.; Adilxodjaev, A.I; Kadirov, I.A. (INTERNATIONAL CONFERENCE ON MULTIDISCIPLINARY RESEARCH AND INNOVATIVE TECHNOLOGIES, 2021)
This article covers the composition, types, properties, production efficiency, strength levels, production of lightweight concrete using aggregates, and many other issues.